The Local Economic Innovation: Lesson from Rotan Ketak Industry in Central Lombok Regency, Indonesia - Asnita Frida Sebayang; Imam Indratno; Lesta Karolina Sebayang (Yayasan Riset dan Pengembangan Intelektual, 2020)
The Rotan Ketak (local rattan) industry is an industry born as handicraft industry with strong local cultural capital. The strengths of this industrial value are; the involvement of women in the production process, environmentally friendly (zero waste), has a value-added network of raw materials, has a high local value from the design aspect, and has a strong network of markets both at domestic and abroad. This study uses a descriptive explanatory method by applying several approaches namely; canvas model business, industrial process analysis, and content analysis. Some important findings of this study describe the ability of the local industry to provide specific added value. Rotan Ketak Industry innovation system can be a source of local economic competitive advantage in facing the global market. The strong value proposition of the product could compete with another product. The industry is also capable to expose some strength of the human side that cannot be completely replaced by the function of sophisticated technology because it combines local values, humanity, art, and local economy. The capacity of this industry to build partnerships between artisans with the local trading system is also a major finding. In the medium-long term, this industry has a potential contribution to achieving local sustainable economic growth.